Factors Affecting Tourists’ Satisfaction and Intention to Return a Destination: Measurement and Implications for Vietnam - Quang, Thang Dao; Thai, Dung Nguyen; Kim, Oanh Thai Thi; Thuy, Van Hoang Thi (International Review of Management and Marketing, 2026)
The study focuses on measuring factors affecting tourists’ satisfaction and intention to return to a destination in Vietnam. The theoretical model is built on basement of “Expectation - Perception,” American Customer Satisfaction Index (ACSI), European Customer Satisfaction Index (ECSI) and Holsat, suitable for the context of Vietnam tourism. Through surveying 398 observation samples using SPSS 29 and AMOS 29 software, testing unidirectional, multidirectional concepts and SEM linear structural model, the study has shown that tourists’ satisfaction and return intention to the destinations in Vietnam is not only directly affected by destination image, perceived service quality, perceived value, perceived attractiveness, but also indirectly affected by expectations. The conclusions of the model are valuable in proposing management implications for tourism service businesses, destination managers and state tourism management agencies in Vietnam.